Repression, resistance and lifestyle: charting (dis)connection and activism in times of accelerated capitalism. - Kaun, Anne; Treré, Emiliano (Social Movement Studies)
Studying the nexus of media and social movements is a growing subfield in both media and social movement studies. Although there is an increasing number of studies that criticize the overemphasis of the importance of media technologies for social movements, questions of non-use, technology push-back and media refusal as explicit political practice have received comparatively little attention. The article charts a typology of digital disconnection as political practice and site of struggle bringing emerging literatures on disconnection, i.e. forms of media technology non-use to the field of social movement studies and studies of civic engagement. Based on a theoretical matrix combining questions of power, collectivity and temporality, we distinguish between digital disconnection as repression, digital disconnection as resistance and digital disconnection as performance and life-style politics. The article discusses the three types of digital disconnection using current examples of protest and social movements that engage with practices of disconnection. Abbreviations: AFA: Anti-Fascist Action; CHRI: Center for Human Rights in Iran; DDoS: Distributed Denial of Service